Biosurfactants : production and utilization--processes, technologies, and economics - Kosaric, Naim, 1928-; Vardar-Sukan, Fazilet, 1956- (CRC Press, 2015)
"Biosurfactants can successfully replace and augment the properties of chemically synthesized surface-active agents. This book contains specialty chapters dealing with methods for production of biosurfactants on a laboratory and industrial/commercial scale. It presents novel and proven applications of biosurfactants. The new edition is aimed at actual production and applications of biosurfactants in modern biotechnology, reflecting the advances made since the publication of the first edition. A special chapter is devoted to the overview and evaluation of specific selected patents relating to biosurfactants"-- Provided by publisher
Keywords: Biosurfactants.; elektronické knihy; electronic books